Characterization of micro grinding tools using optical profilometry. (October 2019) - Setti, Dinesh; Kirsch, Benjamin; Aurich, Jan C.
Highlights: A method was proposed to characterize the electroless plated micro grinding tools using an optical profilometer. 'Volume ratio' was defined for the micro grinding tools considering Abbott firestone curve parameters. Micro grinding tools were classified according to their planer grit density. The proposed method was demonstrated on micro grinding tools with different diameters, grits size, and grits distribution. Abstract: This article presents a method to characterize electroless plated micro grinding tools using an optical measuring device. Abbott Firestone curve characteristics, such as height distribution, void volume, and material volume obtained from topography measurements, were used to define "volume ratio." This parameter distinguishes the micro grinding tools according to their planar grit density. As a result, micro grinding tools can be classified in a manner similar to conventional grinding wheels.